“The Role of Visual Arts in Developing Creative and Critical Thinking in School and Higher Education” - Aslonova Shaxnoza Islom qizi (O‘RTA OSIYODA IJTIMOIY VA GUMANITAR TADQIQOTLAR, 2025)
Abstract: This article examines the role of visual arts in fostering creative and critical thinking among students in school and higher education. It highlights how early engagement in artistic activities enhances cognitive, aesthetic, and problem-solving skills, which are further developed in higher education. The study emphasizes the importance of integrating visual arts across educational levels to promote comprehensive student development and prepare them for professional artistic careers.